DEFORMATION MONITORING OF HIGH-LATITUDE PERMAFROST REGION OF NORTHEASTERN CHINA WITH TIME SERIES INSAR TECHNIQUE - T. Qu; Q. Xu; W. Shan; Z. Li; M. Shan; K. Dai (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
Permafrost distributed in northeast China is the only high-altitude permafrost in China. The deformation monitoring over this permafrost region is of great importance to local climate change and ecological environments. This study focuses on the deformation monitoring of high-latitude permafrost in northeast China with time series InSAR technique. The spatial distribution characteristics, the annual deformation rates and the temporal deformation evolutions of permafrost could be retrieved from multi-temporal InSAR processing with Sentinel-1 TOPS datasets. This work concludes that time series InSAR technique could help to retrieve a comprehensive and reliable permafrost deformation, while a long time-series of displacements facilitated to better understand permafrost kinematics.